The effects of the COVID-19 lockdown on physical activity and sleep quality among university students: cross sectional study - Rehman, Mehroze; Shaikh, Areeba; Maheen, Maryam; Nini, Duaa; Zulfiqar, Bushra; Fawad, Bina (International Journal Of Community Medicine And Public Health, 2022)
Background: Since the commencement of the lockdown, universities shifted their teaching online as an all-out effort to prevent transmission of the infection. This confinement has resulted in poor sleep quality (SQ) and low physical activity (PA) levels. The aim of this study is to determine the effects of the lockdown on SQ and PA levels and investigate their association amongst university students. Methods: 404 students filled out an online questionnaire, the International physical activity questionnaire (IPAQ) and the Pittsburgh sleep quality questionnaire (PSQI), which were used to assess both the parameters. Results: The pandemic resulted in participants indulging in reduced PA and poor global PSQI scores. It was found that females had worse global PSQI scores than males. Furthermore, a significant association was analyzed between SQ and PA where it was seen that participants with worse SQ were involved in low PA during lockdown. Conclusions: The lockdown has been an unfamiliar period in which many lifestyle changes were noted. This study bridges the gap existing in the health education sector and increases awareness among young adults regarding healthy lifestyle choices during this pandemic and forthcoming events.